1962
DOI: 10.1192/bjp.108.452.95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LSD-25 on Relatives of Schizophrenic Patients

Abstract: Schizophrenic patients given LSD-25 show an increase of psychopathological phenomena and a regression to the prime stage of their psychosis, the manifestations of which seem to be more directly related to the life history of the patients.∗ It has also been observed that some “normal” experimental subjects show various paranoid symptoms with the same drug, but whether these are in any way determined by heredity is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…One of the most significant potential psychological side effects after the ingestion of psychedelic compounds in uncontrolled settings is the onset of a psychotic episode, which can last for several hours or days after the drug has worn off. The most vulnerable patients to the onset of long-lasting psychoses appear to be those who have previously received a diagnosis of SCZ, BD, or personality disorder or patients more inclined to mistrustfulness, fearfulness, and susceptibility on projection as defense (Anastasopoulos and Photiades, 1962;De Gregorio et al, 2016a. Other risk factors include mixing other psychoactive substances, such as cannabis.…”
Section: B Acute Side Effects Encountered In Uncontrolled Settingsmentioning
confidence: 99%
“…One of the most significant potential psychological side effects after the ingestion of psychedelic compounds in uncontrolled settings is the onset of a psychotic episode, which can last for several hours or days after the drug has worn off. The most vulnerable patients to the onset of long-lasting psychoses appear to be those who have previously received a diagnosis of SCZ, BD, or personality disorder or patients more inclined to mistrustfulness, fearfulness, and susceptibility on projection as defense (Anastasopoulos and Photiades, 1962;De Gregorio et al, 2016a. Other risk factors include mixing other psychoactive substances, such as cannabis.…”
Section: B Acute Side Effects Encountered In Uncontrolled Settingsmentioning
confidence: 99%
“…hallucinations and delusions) comparable to those seen in drug-naive first-episode schizophrenia patients (Geyer and Vollenweider, 2008; Gonzalez-Maeso and Sealfon, 2009b; Geyer et al, 2012) through a mechanism that involves activation of the 5-HT 2A receptor in cortical glutamatergic neurons (Beique et al, 2007; Gonzalez-Maeso et al, 2007; Celada et al, 2008). It has also been suggested that relatives of schizophrenic patients are more susceptible to the psychotic responses induced by LSD (Anastasopoulos and Photiades, 1962). Although LSD-like drugs as a model of psychosis have limitations (Hays and Tilley, 1973), these findings suggest that a better understanding of their molecular mechanism of action may provide additional insights into the brain processes underlying non-drug-induced psychoses.…”
Section: Pharmacological Models Of Psychosis and Antipsychotic Drug Amentioning
confidence: 99%
“…Hallucinogenic drugs aggravate psychosis in schizophrenia patients (Hoch et al, 1952). Of particular interest is also the finding of hallucinogenic (LSD)-induced psychotic symptoms in relatives of schizophrenic patients (Anastasopoulos and Photiades, 1962), suggesting that individuals with greater predisposition to schizophrenia are more susceptible to the psychotic responses that require activation of the 5-HT 2A R. In murine models, we and others have demonstrated that 5-HT 2A R-regulated pathways on cortical pyramidal neurons are necessary to mediate the signaling pattern and behavioral responses to hallucinogenic drugs (see [Gonzalez-Maeso and Sealfon, 2009] for review).…”
Section: Introductionmentioning
confidence: 99%